Kawing Soro’ dalam Tinjauan Fikih Munakahat (Studi Kasus di Desa Citta Kecamatan Citta Kabupaten Soppeng): Kawing Soro' in the Review of Fikih Munakahat (A Case Study in Citta Village, Citta Sub-District, Soppeng District) - Rosmita; Syamsiah Nur; Annisa Fausya (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2026)
This study aims to find out and understand the soro' marriage in the perspective of munakahat fiqh. The problems that the author raises from this study are: first, how is the concept of soro' marriage in Citta village, Citta sub-district, Soppeng district; and second, how is the view of munakahat fiqh towards soro' marriage in Citta village, Citta sub-district, Soppeng district. This study uses a qualitative research type using a normative approach method, a phenomenological approach, and a sociological approach. The results of the study found are as follows: first, the concept of soro' marriage consists of objectives, pillars, requirements for both brides and grooms, requirements for guardians, requirements for witnesses and stages of soro' marriage. Second, the law of soro' marriage is permissible or the marriage is valid according to the view of munakahat fiqh, because there is no difference between the pillars and requirements in marriage, except in the stages of soro' marriage, namely mappacci, mappassikarawa, good days and twin marriage. This is contrary to Islamic law so that it is forbidden to do it. Even though these stages are forbidden, the marriage is still valid. Because these stages are only traditions that when abandoned do not cancel the marriage. The implications of this study are expected so that society is more careful and it would be better to abandon these stages and switch to Islamic marriage as exemplified by the Prophet Muhammad.